Problems in Community-Based Waste Management - Noventi, Ike Arni (Jurnal Ilmiah Administrasi Publik, 2020)
The paradigm shift in waste management has encouraged a change in waste management to be more community-based by reusing waste through waste banks. This study aims to describe the various waste management problems faced by the Matahari Waste Bank, Madiun City. Descriptive research method with qualitative approach is used in this research. The result shows that the waste bank faces problems include a lack of human resources, limited knowledge and skills of waste bank management, inadequate waste management infrastructure, lack of support from local government, and a lack of public understanding of the importance of waste banks. Local governments need to make concrete efforts in encouraging and supporting waste management through waste banks as mandated by laws and government regulations and as a form of appreciation for the waste bank.